Exploiting core-shell motif for new synthetic methodologies of nanostructures - Wang, Hong (2013)
This thesis summarizes my postgraduate research on the exploration of basic mass transport phenomenon at nanoscale, the development of advanced assembly strategies for well-defined complex nanostructures, and the design of novel methodologies for the synthesis of hybrid nanostructures. The research was carried out based on core-shell nanostructures, where the metal core is encapsulated with amphiphilic diblock copolymer shell. In specific, metal-polymer core-shell nanoparticles were synthesized and then served as nanocarriers to elucidate the drug release kinetics. On the other hand, we studied the respond of polymer micelles to the environmental stimuli such as pH, solvent, and ultrasound, in particular, in the presence of embedded metal nanoparticles. It turned out that the structural transformation of polymer shell could facilitate the metal core assemble into a highly order manner. In detail, we performed systematical investigation on the short-distance drug release in the presence of nanoacceptors (Chapter 2). The core-shell AuNP@PSPAA was chosen as nanocarriers, where the fluorescence of model drug (pyrene) could be quenched by the Au core. Thus, pyrene incorporated in AuNP@PSPAA can be readily distinguished from the one released into nanoacceptors or solution, offering a simple system for studying the release kinetics via optical measurements. Introducing nanoacceptors (free PSPAA micelles) into the model system resulted in a rapid release of pyrene owing to concentration gradient. It is found that the rapid release fit well to the Fickian diffusion model and the diffusion of pyrene must be through the water, but not the rate-determining step. Thus, the release kinetics can be described by the radial diffusion from AuNP@PSPAA to free PSPAA micelles. The nanoacceptors were changed to both SDS and bovine serum albumin micelles to well represent cell membrane. The release kinetics was found to be similar in all cases. Polymer micelles display rich structural variety, primarily including sphere, cylinder, and vesicle. These morphologies can transform among themselves in respond to the environmental stimuli. In Chapter 3, we studied the sphere-to-cylinder transformation of PSPAA micelles in response to pH, in particular, in the presence of embedded Au nanoparticles. It turned out that the rearrangement of the polymer shells promoted the assembly of Au nanoparticles into one-dimensional chains. This unconventional aggregation of nanoparticles followed the "chain-growth polymerization" mode, resulting in high structural selectivity which reduces the branches and irregulars. We found that the PSPAA shells played a crucial role in precise controlling the width of the nanoparticle chains and realizing the conversion from single-line chains to double-line chains. Precise controlling the size and structure of metal nanoparticle assemblies could generate desirable optical properties. We developed a new method to control the size and structure of nanoparticle chains assisted by ultrasound (Chapter 4). The PSPAA encapsulated single-line nanoparticle chains broke into short ones as the result of the cavitation. By tuning the ultrasonic energy, the scission rate and the length of the chains were effectively controlled. Interestingly, the nanoparticle chains could reorganize into spherical nanoclusters under a higher ultrasonic energy. We provided the evidence that the formation of 3D nanoclusters involved the scission of the PSPAA shells and the cylinder-to-sphere transformation of the polymer micelles. Our studies showed the mobility and stretching ability of the surface ligand facilitated the organization of nanoparticle chains into 3D nanoclusters. In Chapter 5, we demonstrate a scalable and facile method to the rational fabrication of "nanofish" via swelling the PSPAA micelles. In an emulsion system, the polymerization of oil droplets (divinylbenzen) took place in the polymer shell of AuNP@PSPAA and led to phase separation at nanoscale, thereafter resulting in the formation of anisotropic nanoparticles. The shearing force originated from stirring was regarded to be a critical factor. It controlled the diffusion of oil droplets from aqueous solution into the polymer shell of AuNP@PSAA, which further affected the swelling of polymer micelles and the degree of phase separation. As a result, various types of "nanofish-shaped" nanoparticles were synthesized.